Catatan Pertama Distribusi Tridacna noae (Röding, 1798) dari Perairan Kepulauan Kei, Maluku - Teddy Triandiza; Udhi Eko Hernawan; Agus Kusnadi (Jurnal Kelautan Tropis, 2023)
The giant clams are the biggest  living bivalves that not only play a  vital role in coral reef ecosystem, but also as a food provider for coastal inhabitant. One of these species was Tridacna noae which is a crpyctic species due to morphoplogial characteristic similarity and habitat preferences with Tridacna maxima. Tridacna noae was recorded at the first time found in Kei Islands on November and December 2017 based on morphological characteristic and DNA barcoding analysis. This research found 8 individu of T. Noae in total, 7 individu was found in Kur Island and one individu from Ohoidertom at 2-3 m depth. The mantle pattern of T. noae was very unique and can be used to distinguished from T. maxima. Special feature of ormanent mantle of T. noae indicated with oval-shape patch with white line on the edge, has hyaline organ scattered along the margin of mantle and the presence of papillae that clearly seen. The result on Blasting from GenBank NCBI for COI sequence of giant clam sample revealed that 99.79%-100% was identical with T. noae species. Furthermore, result on genetic distance analysis of T. noae sample from Kei Island compare with T.noae from GenBank was 0.00-0.051, while genetic distance value compare with T. maxima was 0.159 – 0.205. The new finding of T. noae in Kei Island has added the number of giant clam species recorded previously become 7 species. This finding was also has enhanced the information on biogeographical distribution of T.noae in Indonesia.  Kerang kima merupakan kelompok bivalvia berukuran paling besar yang memlilki peranan penting di ekosistem terumbu karang serta menjadi sumber nutrisi bagi masyarakat peisir. Salah satu species kima adalah Tridacna noae yang bersifat cryptic spesies karena memiliki banyak kesamaan karakteristik morfologi dan preferensi habitat dengan T. Maxima. T. noae tercatat pertama kali ditemukan di Perairan Kepulauan Kei pada bulan November dan Desember 2017 berdasarkan pengamatan karekteristik morfologi dan aplikasi DNA barcoding. Hasil peneltian menemukan delapan individu T. noae, tujuh individu ditemukan di Perairan Pulau Kur, satu individu ditemukan di Perairan Ohoidertoom dengan kedalaman perairan 2-3 m. Ornamen mantel T. noae sangat khas dan dapat digunakan untuk membedakan dari T. maxima. Ornamen mantel ditandai dengan patch berbentuk oval terpisah dengan garis putih di tepi, memiliki organ hialin yang tersebar di sepanjang margin mantel, dan kehadiran papila yang terlihat jelas. Hasil blasting di GenBank NCBI untuk sekuens COI sampel kima menghasilkan tingkat kemiripan 99.79%-100% (identik) dengan T. noae. Hasil analisis jarak genetik sampel T. noae asal Kepulauan Kei dengan T. noae Genbank adalah sebesar 0.00 hingga 0.051, sedangkan jarak genetik dengan T. maxima adalah 0.159 hingga 0.205. Temuan T. noae di Kepulauan Kei menambahkan jenis kima yang tercatat sebelumnya di Kepulauan Kei menjadi 7 jenis. Temuan ini juga menambahkan lebih banyak informasi tentang distribusi geografis T. noae di Indonesia